Increasing principals' time on instructional leadership: exploring the SAM® process. Issue 1 (30th August 2019) - Goldring, Ellen; Grissom, Jason; Neumerski, Christine M.; Blissett, Richard; Murphy, Joseph; Porter, Andrew
Abstract : Purpose: Despite increased focus on the importance of the time principals spend on instructional leadership, there is little research on practical ways to help principals manage their time to achieve this goal. The purpose of this paper is to examine the implementation of the school administration manager (SAM) process: a unique program designed to help principals orient their time toward instructional activities. Design/methodology/approach: This mixed-methods study combines data from multiple sources including: case studies of four districts that involved interviews with principals and program staff in 16 schools; interviews with network-level staff and administrators; a survey of 387 principals and 378 program staff; and time use data collected by shadowers as well as a time-tracking calendar system for 373 principals. Findings: Principals and their teams implemented the SAM process with relatively high fidelity. In addition, most participated in the program to increase time spent on instructional tasks. Indeed, principals' time use shifted from managerial to instructional tasks as they implemented the program. However, there were important challenges related to the time and personnel resources required to implement the program as well as questions about the quality of the instructional leadership time spent. Originality/value: This study describes not only time allocation, but also a process through which principals intentionally sought to shift their time toward instructional leadership activities. The insights gained from the implementation and outcomes of this process provide concrete direction for policymakers, practitioners and researchers looking for ways to change the time principals spend on instructional leadership.